Post-synthetically modified metal–organic framework as a scaffold for selective bisulphite recognition in water. (1st December 2018) - Sen, Arunabha; Desai, Aamod V.; Samanta, Partha; Dutta, Subhajit; Let, Sumanta; Ghosh, Sujit K.
Graphical abstract: A post-synthetically modified MOF has been employed for sensing of bisulfite anion in water medium. This MOF based selective turn on response towards bisulfite anion has also been demonstrated in presence of concurrent anions. Abstract: A metal–organic framework (MOF) based luminescent probe was strategically designed for selective recognition of bisulfite anion (HSO3 − ) in water medium. The chemically stable MOF, NH2 -MIL-68(In) was decorated with specific recognition site via post synthetic modification. The post synthetically modified MOF showed a selective turn on response towards bisulfite anion retaining its structural integrity. This selective recognition is also persistent even in presence of competing anions.